Relationship Satisfaction and Depression After Traumatic Brain Injury: An Actor-Partner Interdependence Model of Patients and Caregivers in Mexico and Colombia. (November 2020) - McKee, Grace B.; Perrin, Paul B.; Rodriguez Agudelo, Yaneth; Olivera Plaza, Silvia Leonor; Quijano-Martinez, Maria Cristina; Ohayagha, Chimdindu; Kuzu, Duygu; Cariello, Annahir N.; Arango-Lasprilla, Juan Carlos
Abstract : Objective: Traumatic brain injury represents a major public health concern, particularly in low- and middle-income countries like in Latin America. Family members are often caregivers for individuals with traumatic brain injury, which can result in significant stress. Research is needed to examine depression and quality of the caregiving relationship in these dyads. This study examined relationship quality and depression longitudinally after traumatic brain injury within the caregiving relationship. Design: Dyads ( N = 109) composed of individuals with traumatic brain injury and their caregivers were recruited from three hospitals in Mexico and Colombia. They self-reported depression and relationship satisfaction during hospitalization and at 2 and 4 mos after hospitalization. Results: A 2-lag Actor Partner Interdependence Model demonstrated that patients and caregivers reporting high relationship satisfaction at baseline experienced lower depression 2 mos later, which then predicted higher caregiver relationship satisfaction at 4 mos. Moreover, patients with high relationship satisfaction at baseline had caregivers with lower depression at 2 mos, which was then associated with patients' higher satisfaction at 4 mos. Conclusions: Within individuals with traumatic brain injury and caregivers, depression and relationship satisfaction seem to be inversely related. Furthermore, patients' and caregivers' depression and relationship satisfaction impact each other over time, demonstrating interdependence within the caregiving relationship.